Sweet Clover (Melilotus spp.) as a Source of Biologically Active Compounds - Patrycja Sowa-Borowiec; Maria Czernicka; Wacław Jarecki; Małgorzata Dżugan (Molecules)
Sweet clover, particularly white sweet clover (Melilotus albus), is an underexplored plant that has gained attention in recent years. This study compared the bioactive compounds content in the flowers, leaves, and stems of Melilotus albus Medic. to the well-known health-promoting Melilotus officinalis (L.) Lam. Both fresh and dried plant materials were analysed, with chromatographic assessments preceded by the optimisation of the extraction method (using 50% aqueous ethanol–water and the plant sample ground in a mortar, followed by 30 min of ultrasound-assisted extraction). Flower and leaf extracts were also evaluated for their total phenolic content (TPC) and antioxidant activity using FRAP and DPPH· assays. Both plant species were rich in phenolic compounds, including coumarins, phenolic acids, and flavonoids. HPLC-PDA analysis revealed similar profiles for both species, with quantitative differences in individual compound fractions. The highest coumarin content was found in the fresh flowers, followed by the leaves and stems. No significant species-specific differences in the coumarin content were observed. However, the flowers of M. albus were a richer source of flavonoids, with the highest hyperoside content. The flavonoid profile in the leaf extracts was similar to that of the flowers, but the content was about four times lower in the leaves and even lower than in the stems. Interestingly, the leaf extracts exhibited higher antioxidant activity than the flower extracts. The presented findings suggest that white sweet clover is an equally valuable source of health-promoting compounds as yellow sweet clover.